The Bankers' Blacklist : Unofficial Market Enforcement and the Global Fight against Illicit Financing - Morse, Julia C. (Book collections on Project MUSE., 2021)
"In recent years, international regulation has caused big banks to cut thousands of cross-border relationships with overseas banks. Domestic banks in those countries cannot afford to be cut off from global financial markets and so become advocates for more regulation. A 39-member intergovernmental body, the Financial Action Task Force (FATF), has enlisted cross-border banks to keep 'bad money' out of the financial system"--